On the epistolography of Michael Glykas - KIAPIDOU, Eirini-Sophia (Byzantina Symmeikta, 2012)
Michael Glykas’ collection of ninety-five letters proves to be a core element of his work, and one that needs to be studied as a whole, in conjunction with his better-known chronicle, so that more light can be shed on the ambiguous data of this scholar’s highly interesting life and thought as well as the literary production of the Byzantine 12th century.